POLLUTION LEVEL ASSESSMENT OF ROAD DUST FROM ISLAMABAD EXPRESSWAY - Faiz, Y.; Siddique, N.; Tufail, M. (The Nucleus, 2013)
Thirteen road dust and four soil samples were analyzed using Instrumental Neutron Activation Analysis (INAA) and Flame Atomic Absorption Spectroscopy (FAAS) to determine the elemental composition of road dust collected from Islamabad Expressway. Pollution parameters and indicators such as Enrichment Factors (EFs), Pollution Load Index (PLI), Geoaccumulation Index (Igeo), Pollution Index (PI) and Integrated Pollution Index (IPI) were calculated and showed that the area around Islamabad Expressway is low to moderately polluted especially by elements such as Mg and Sb. The IPI of the elements was found to vary in the order; Mg>Sb>Cu>Sr Pb>Ga>Na >Sn Zn>Yb>Se>Hf. The 5 samples collected around the busy intersections of Faizabad and Zero Point have higher amounts of most of the elements determined. Moreover the pollution indices for these samples indicate that these sites are more contaminated than the remaining 8 sampling sites.